The Effect of Fly Swatter Game on Students Vocabulary Mastery At First Grade Students of SMPN 1 Inuman-Kuantan Singingi - Parni Meri, Elatri; Hilma Pami Putri; Loli Safitri; Reflinda (Yayasan Lembaga Studi Makwa, 2022)
The researcher conducted this research because researcher found several problems in the process of learning English. Those problems were related through observation in the class at SMPN 1 Inuman-Kabupaten Kuansing. The first is that the students have difficulty learning English. The second is that most of students lack vocabulary. The third is that the teacher uses monotone techniques in learning English, especially vocabulary. In this case, this research was going to find out whether there was a significant effect of the fly swatter game on students’ vocabulary mastery in first grade students of SMPN 1 Inuman-Kabupaten Kuansing. The researcher used quantitative research as the methodology for this research, as well as experimental research. The design of this research was pre-experimental research with one group pretest-posttest design. The subjects in this research were all of the students in first grade at SMPN 1 Inuman. The researcher used the random sampling technique in taking the sample, in which the VIIB class became the sample of the research, which consisted of 19 students. The data was gotten from the students’ vocabulary tests that were given before and after treatment was given. After calculating the data, it was found that the mean score of the students’ vocabulary mastery on the pre-test was 62.10, while the mean score of the students’ post-test was 73.95. It means that the fly swatter game had a significant effect on students' vocabulary mastery in first grade students of SMPN 1 Inuman-Kabupaten Kuansing. Abstrak Peneliti melakukan penelitian ini karena peneliti menemukan beberapa masalah dalam proses pembelajaran bahasa Inggris. Permasalahan tersebut terkait melalui observasi di kelas di SMPN 1 Inuman-Kabupaten Kuansing. Yang pertama adalah siswa mengalami kesulitan belajar bahasa Inggris. Kedua, sebagian besar siswa kurang kosa kata. Ketiga, guru menggunakan teknik monoton dalam pembelajaran bahasa Inggris, khususnya kosa kata. Dalam hal ini, penelitian ini akan mencari tahu apakah ada pengaruh yang sig+nifikan dari permainan pemukul lalat terhadap penguasaan kosakata siswa pada siswa kelas satu SMPN 1 Inuman-Kabupaten Kuansing. Peneliti menggunakan penelitian kuantitatif sebagai metodologi penelitian ini, serta penelitian eksperimental. Desain penelitian ini adalah penelitian pra eksperimen dengan desain one group pretest-posttest design. Subjek dalam penelitian ini adalah seluruh siswa kelas I SMPN 1 Inuman. Peneliti menggunakan teknik random sampling dalam pengambilan sampel, dimana kelas VIIB menjadi sampel penelitian yang berjumlah 19 siswa. Data diperoleh dari tes kosakata siswa yang diberikan sebelum dan sesudah diberikan treatment. Setelah menghitung data, ditemukan bahwa rata-rata skor penguasaan kosakata siswa pada pre-test adalah 62,10, sedangkan skor rata-rata post-test siswa adalah 73,95. Artinya permainan pemukul lalat berpengaruh signifikan terhadap penguasaan kosakata siswa kelas I SMPN 1 Inuman-Kabupaten Kuansing.